(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article studies the theoretical and practical aspects of the application of the contextual learning model in the modern education system, the main features and advantages of contextual learning, including linking theoretical knowledge with practice, increasing student interest, introducing a person-centered educational approach and strengthening professional training, didactic and methodological aspects of the contextual learning process, the advantages of interdisciplinary integration and the stages of its implementation in practice. The role of this approach in training competitive personnel in the labor market is also emphasized. The article is of great importance as a scientific basis for the implementation of innovative methods that serve to improve the pedagogical process and improve the quality of education.